OPTIMALISASI PENGELOLAAN SAMPAH DI TPA TAMBAKRIGADUNG KECAMATAN TIKUNG KABUPATEN LAMONGAN - Auvaria, Shinfi Wazna; Nisaul Fitrotul Jannah; Amrullah (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2024)
The increase in population affects the production of waste produced. However, in the last 4 years, waste management at the Tambakrigadung landfill has not manage well. This research aims to analyze the generation, composition of waste, analysis and evaluation of waste management in landfills based on PU Ministerial Decree NO. 03 of 2013, as well as optimizing waste management at Tambakrigadung landfill. Based on research results, the average amount of waste generated at Tambakrigadung landfill is 21,510 kg/day, the average density is 263.82 kg/m3, the largest waste composition is organic waste with a percentage of 65% of all types of waste. From the results of this analysis, optimizing the landfill requires increasing the land area in certain buildings, such as operational roads measuring 1 meter, adding a sorting building by building a TPST in the landfill, and recording the transportation of waste trucks, the source of the waste and the weight of the waste. Optimalization in Non-technical aspects, landfill requires an SOP for how to work and an SOP for using tools.